2004
DOI: 10.1186/1471-2490-4-4
|View full text |Cite
|
Sign up to set email alerts
|

The urine dipstick test useful to rule out infections. A meta-analysis of the accuracy

Abstract: Background: Many studies have evaluated the accuracy of dipstick tests as rapid detectors of bacteriuria and urinary tract infections (UTI). The lack of an adequate explanation for the heterogeneity of the dipstick accuracy stimulates an ongoing debate. The objective of the present meta-analysis was to summarise the available evidence on the diagnostic accuracy of the urine dipstick test, taking into account various pre-defined potential sources of heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
286
3
19

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(325 citation statements)
references
References 71 publications
17
286
3
19
Order By: Relevance
“…This first step should generate very few false-negative results and should have a high negative predictive value. However, screening by dipstick alone carries the risk of missing infections and other urinary diseases (13)(14)(15)(16). In this study we confirmed the low sensitivity and negative predictive value of this traditional approach and found that screening by dipstick combined with automated urine analysis strongly reduced the rate of false-negative results.…”
Section: Discussionsupporting
confidence: 75%
“…This first step should generate very few false-negative results and should have a high negative predictive value. However, screening by dipstick alone carries the risk of missing infections and other urinary diseases (13)(14)(15)(16). In this study we confirmed the low sensitivity and negative predictive value of this traditional approach and found that screening by dipstick combined with automated urine analysis strongly reduced the rate of false-negative results.…”
Section: Discussionsupporting
confidence: 75%
“…The reagent strip has not only been used to rule out urinary tract infections for a long time with similar performance of detecting this kind of infection [23], but also to help diagnose patients with other biological fluid infections such as meningitis and empyema [16][17][18]. The use of those strips in ascitic fluid has had good results in the diagnosis of peritonitis in patients on peritoneal dialysis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…All patients had their urine screened with dipstick testing. This has previously been shown to be a reliable screen [5], and positive samples were sent for culture and microscopy. In line with local policy 105 organisms/ml was defined as a positive culture.…”
Section: Methodsmentioning
confidence: 99%